Cardiac tamponade in a patient with ankylosing spondylitis: a notable response to TNF inhibitors. (11th August 2018) - Kwan, Clara; Martirossian, Linett; Scheers-Masters, Joshua; Hollander, Gerald
Abstract : Ankylosing spondylitis (AS) is a rheumatological disorder of the spine, and like many other rheumatological diseases, it can manifest as a systemic inflammation. We present a rare case of cardiac manifestations of AS in a 25-year-old man with recurrent chest pain and pericardial effusions. He initially presented with pleuritic chest pain, was diagnosed with cardiac tamponade and required emergent pericardiocentesis. The patient returned again with chest pain and was found to have reaccumulation of pericardial effusion. The cardiac symptoms were finally resolved when he was diagnosed and treated for AS.